Pentingnya Ownership Concentration Dan Free Cash Flow Pada Divident Payout - Jeslyn, Jeslyn; Dewi, Sari; Karjantoro, Handoko (GEMA EKONOMI, 2023)
The purpose of this study is to analyze the relationship between capital structure, corporate governance on company performance which is controlled by several other factors. The capital structure in this study is represented by ownership concentration and free cash flow. In this study, there are several control variables used including firm size, firm age, growth and risk. The results of statistical tests show that the variables of ownership concentration, free cash flow, firm size, firm age, growth and risk have no significant effect on dividend payout.